Nucleosome fragility reveals novel functional states of chromatin and poises genes for activation - Xi, Yuanxin; Yao, Jianhui; Chen, Rui; Li, Wei; He, Xiangwei (Genome Research, 2011)
The structural complexity of nucleosomes underlies their functional versatility. Here we report a new type of complexity - nucleosome fragility, manifested as high sensitivity to micrococcal nuclease, in contrast to the common presumption that nucleosomes are similar in resistance to MNase digestion. Using differential MNase digestion of chromatin and high-throughput sequencing, we have identified a special group of nucleosomes termed fragile nucleosomes throughout the yeast genome, nearly one thousand of which at previously determined "nucleosome free" loci. Nucleosome fragility is broadly implicated in multiple chromatin processes, including transcription, translocation and replication, in correspondence to specific physiological states of cells. In the environmental-stress-response genes, the presence of fragile nucleosomes prior to the occurrence of environmental changes suggests that nucleosome fragility poises genes for swift up-regulation in response to the environmental changes. We propose that nucleosome fragility underscores distinct functional statuses of the chromatin and provides a new dimension for portraying the landscape of genome organization.